MODELING FERTILITY RATE OF INDONESIA IN THE PRESENCE OF INTERFERENCE: THE 2004 TSUNAMI. - Akoth, Odero Everlyne; Onyango, Fredrick O.; Otumba, Edgar O. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
A lot of studies have been done on fertility for many years. But, scarce literature is found on modeling of fertility in the presence of interference, yet interference to fertility is a common phenomenon. This study focused on modeling of fertility rate in the presence of interference. We have fitted Probability distributions to interference free data set of Indonesia 2002 and also to the Indonesia 2007 fertility data set which had interference in it, so as to determine the effect of interference on the shape of the fertility data. The parameter of the distributions were estimated and then fitted by maximum likelihood estimation available in the `fitdistr’ package, in the R statistical software. The model life table approach was also used to determine the net fertility value F0 which was modeled from the net reproduction value R0. A relationship between fertility rate in the presence of interference and population growth was then established. A major finding of this study is that interference free fertility data fit a gamma distribution, data containing interference fit a modified gamma distribution with a mounded but skewed shape. The results also showed that in the presence of interference F0 >2, hence population increases. Results of this study would help demographers and businessmen to deal with random factors that affect all areas of demography and businesses striving to succeed in today’s highly competitive environment. Probability distribution is a scientific tool that would help demographers and business persons to deal with uncertainty and hence make informed decisions. The modeling results would protect demographers from potential time and money loss which might arise due to invalid model selection thereby, helping the Government in planning for social amenities for its citizens.